Table of Content - - (Journal of Educational and Psychological Sciences, 2025)
Table of Content: The Role of Knowledge Management in Achieving the Sustainable Competitive Advantage for Secondary Schools in Riyadh City Ms. Nouf Hameed Almohammadi The Reality of Digital Transformation in Jordanian Schools from the Point of view of Teachers Ms. Marwa Mohammad Al-Qatarneh ,Dr. Fatima Abd Alkareem Wahba The role of bilingual education in promoting cultural diversity among school students In the Interior of Palestine from the Teachers’ Perspective Ms. Shireen Saed Abbas Reasons for the Decline in the Planning Standard in School Evaluation Results: from the Perspective of School Principals in the Tan’eem Education Office, Makkah Mr. Ali Atiyah Ali Al-Malki Research trends related to the role of artificial intelligence in improving blended learning practices at the undergraduate level Ms. Ghzail Fahad Aldossari, Ms. Sarah Misha’i Al-Dosari Difficulties Facing Strategic and Educational Planning in the Ministry of Education in Palestine state Mr. Mahmoud Hoseen Alajjouri Psychometric Properties of the Stress Coping Strategies Scale for Adolescents Mr. Muhammad Yahya Al-Hazzazi, Prof. Saleh Yahya Al-Ghamdi